Hidden support for the lionesses: a breast/bra intervention - Wakefield-Scurr, J.; Jones, M.; Jones, B.; Whatling, E.; Mehta, R. (Research in Sports Medicine, 2025)
Despite health and performance benefits of appropriate breast support in sport, elite women athletes` knowledge of breasts/bras is poor leading to poor bra choices, breast pain and performance decrements. This multiphase intervention assessed breast/bra issues and preferences, individually prescribed sports bras and evaluated outcomes for the England Senior Women footballers. Breast/bra workshops were delivered to England players; all 36 completed pre-intervention surveys and breast/bra assessments, before being prescribed bras six weeks before European and World Championships (2022, 2023). 24 players completed post-intervention surveys. Pre-intervention outcomes identified poor knowledge, poor bra fit, many bra issues, and cultural sensitivities. Breast pain was prevalent (61%), with 25% reporting clinically significant breast pain. Post-intervention, players reported significant improvements with prescribed sports bras. 91% reported improvements in knowledge and benefiting from the intervention. This successful intervention provided an evidence-base for ongoing breast health initiatives with England Teams, plus roll-out to all levels of women`s football.